Post-crisis health reality and wellbeing of children within Syria: a scoping review of research from 2012 to 2024 - Seba Harphoush; Fatema Ahmed; Ihab Harphoush; Rasha Kadoun; Soha Harphoush; Rami Al Asaad; Zhong Li (Conflict and Health)
Abstract Background Syrian children, among the most vulnerable groups, have faced profound physical and psychological consequences due to the protracted conflict. This review assesses the health and well-being of children living within Syria, with particular attention to internally displaced populations (IDPs). Objectives To synthesize research on child health in Syria from 2012 to 2024, identify key health challenges, assess study characteristics and geographical distribution, and highlight gaps to inform future policies and interventions. Design We conducted a scoping review in December 2024 using the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) methodology. We searched five academic databases (Medline Ovid, PubMed, Scopus, Web of Science, and Global Health) and selected studies published between January 2012 and December 2024. The search strategy followed the JBI Population–Concept–Context framework. Eligible studies included primary and secondary research, published in English or Arabic, that examined the health of children under 19 years old living within Syria in the context of the ongoing conflict. Grey literature was also retrieved from major organizational repositories (e.g., WHO, UNICEF, MSF, SAMS). Results A total of 1,189 records were retrieved, with 647 remaining after removing duplicates. After screening, 30 studies met the inclusion criteria. Most were observational, including cross-sectional (63.3%) and retrospective cohort (26.7%) designs. Surveys and medical records were the main data sources; oral examinations were common in dental studies, while anthropometry, blood tests, and interviews were less frequent. Data sources varied significantly by region (p < 0.001), with government-controlled areas relying on state institutions and non-government-controlled areas drawing on humanitarian data. Due to substantial heterogeneity, meta-analysis was not feasible. Notably, 80% of studies reported no external funding. Conclusion This review highlights major research gaps in child health within Syria, particularly among IDPs and in underserved regions. Most studies were observational, unfunded, and regionally concentrated, limiting broader applicability. Despite these constraints, this is the first comprehensive synthesis of health research focused on children within Syria, providing a foundation for future research, policy action, and targeted humanitarian interventions in conflict-affected settings.